Slum Study in Surat - Centre for Social Studies (World Bank, Washington, DC, 2013)
This report discusses the study of slums in the city of Surat and it is divided into eight sections. Section one introduces the study and discusses general background, overall methodology, methods and techniques of data collection, and methods of analysis; section two profiles the city of Surat and slums therein; section three discusses definition and recognition of slums and situation of tenure of land along with the physical and social infrastructure and people's views on the same; section four attempts to throw light on resettlement and up-gradation of slums and section five relates with the community participation and activities in the slums. The objectives of these studies of slums in four towns/cities were as follows: The similarities and differences identified may be in perceptions of slum dwellers about the priority of services in the slum, their economic condition, economic potential and willingness to share the cost of internal infrastructure and community dynamics including the degree or potential for community organization, mobilization or group savings, etc.